'The Taxidermist's Daughter' - Francesca Rhydderch (The BBC National Short Story Award 2014, 2014)
‘The Taxidermist’s Daughter’ is a short story set in a west Wales seaside town shortly after the First World War. A girl in her early teens, Daisy, is employed by her father to help him with his taxidermy business, but she is only ever allowed to paint and decorate the glass cases, never to touch the birds and small animals preserved and sold by her father. The arrival of a curious professor of Natural History causes seismic shifts in the close-knit family, who are still mourning the loss of Daisy’s brother, David, at the Battle of the Somme. New worlds open up to Daisy, but much as she had yearned to grow up, moving into adulthood proves a painful process.